Genótipos de aveia branca (Avena sativa L.) submetidos a diferentes protocolos e doses de alumínio em cultivo hidropônico. - Crestani, Maraisa (2008)
The ability to perform experiments under controlled conditions employment of evaluations in controlled environment such as hydroponic culture has attracted crop breeders attention regarding the selection of aluminum (Al) tolerant plants. This strategy facilitates the detection of plant injuries in early stages of development, representing a non-destructive method. Also, the results obtained are highly correlated to field performances of tested genotypes. Different methods have been used to study aluminum tolerance in hydroponic conditions. However, it is necessary to improve the understanding of these techniques in order to optimize their efficiency. Stalling of root growth has become the basis of major procedures evaluating aluminum tolerance of white oat genotypes in hydroponic culture. However, the expression of other characters in plantlets can be associated to tolerance and may turn out to facilitate the indirect selection for this character. Also, this could lead to the adoption of analyses involving all morphological characters. Therefore, standard white oat genotypes were subjected to different methods and Al levels under hydroponic conditions aiming to establish the most effective technique to identify superior aluminum tolerant plants based on root length. In addition, this study aimed to verify the relationship between plantlet characters and their performance in the aluminum tolerance characterization using multivariate statistics. The experimental design was complete randomized blocks with three replications, using three methods: complete nutrient solution with 0, 8, 16 and 32 mg L-1 of Al supplied as Al2(SO4)3.18H2O; complete nutrient solution with 0, 8, 16 and 32 mg L-1 of Al supplied as Al2Cl3.6H2O; and the minim nutrient solution with 0, 1, 3 and 5 mg L-1 of Al supplied as Al2Cl3.6H2O. The complete nutrient solution methods are efficient to identify aluminum tolerant white oat genotypes based on root length. The performance of the plantlet characters is highly correlated with root length in white oat genotypes subjected to the aluminum stress under hydroponic conditions. The nutrient composition and the Al sources employed influence the plant responses. The study based on the joint analysis of plantlet characters does not allow the efficient discrimination of white oats genotypes regarding their level of aluminum tolerance in hydroponic culture when there is a relationship of dependence between the variables.